Diseminasi Layanan Digital berbasis Artificial Intelligence di Kelurahan Tompokersan Lumajang Untuk Mendukung Terwujudnya Tata Kelola Inovatif - Lukman Hakim; Husin Husin; Choirul Huda; Denny Wijanarko; Dhony Manggala Putra; Muhammad Aiman; Audrey Pramudita Sudarmanto; Nabila Tri Andita Ramadani (Indonesian Journal Publisher, 2025)
Village Government is a miniature of the state and the front door after the family to build Human Resources (HR). One of the aims of the state is to provide service functions to the community. Tompokersan village, Lumajang has implemented technology in its certificate-making services. The existing services are less effective because letter submitting still uses Google Forms. The service has several weaknesses, namely does not have a queue mechanism for submitting certificates, cannot prevent unauthorized users, submission data is not integrated, does not have AI-based customer service such as chatbots, and RT/RW heads carry out manual approval. This is considered less effective and has not been fully digitized. This makes the governance of Tompokersan Village less good. Tompokersan village requires a web and mobile-based information system that can solve these problems. Several certificates are usually made by the village, including a business certificate, a domicile certificate, a certificate of not being married, a certificate of being unable to pay, a death certificate, a birth certificate, and other certificates. This service aims to realize innovative governance in the Tompokersan village. The results of the dissemination of Digital Services can solve partner problems, namely reducing queues at the sub-district office, validation by RT and RW heads can be done digitally, sub-district officers can easily record and report, and the public can participate in monitoring the status of letters that have been submitted via the mobile application.